A Study on Aircraft Heating System Trainer Model AS-43 for Aeronautical Engineering Students Practice - Pisal, Fatin Auni; Nor Salim, Nor Adrian (Progress in Aerospace and Aviation Technology, 2023)
The Model AS-43 Heating system trainer is a fully operational model of a light aircraft heating system demonstrating the combustion air heater method. Heat transfer is related to the mechanism that happens in this process. This study aims to utilize the Trainer Model AS-43 for practical experiments in aeronautical engineering education. The research objectives include developing standard operating procedures, determining system parameters, and proposing improvements. The significance of the study lies in enhancing the teaching scope for aeronautical engineering students and improving the Aircraft Heating System Trainer Model AS-43. The obtained results and calculations serve as valuable data for aeronautical engineering education and can facilitate further analysis and improvements in the field. Recommendations were made to enhance the trainer’s utilization, including incorporating appropriate measuring tools. Implementing these recommendations would maximize the trainer’s educational potential, allowing it to be utilized as an effective teaching tool for mechanical and aeronautical engineering courses. The proposed changes could improve students’ comprehension, promoting better learning outcomes and advancing aviation education.